No Bystanders Any Longer: Social sciences, social responsibility and sustainability research in an emerging revolution (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2014)
This paper argues that sustainable development in thinking and in practices is the beginning of a revolution, a major societal paradigm shift, which eventually will match the industrial revolution in transforming social, economic, and cultural conditions. The first part of the article discusses several features of this revolution and what it shares with, and how it differs from, the industrial revolution. The second part of the article discusses the role that social sciences in general and sociology in particular can and should play in relation to the revolution of sustainable development, among other things, monitoring and data collection, analyzing, explaining, identifying and providing assessments of social impacts and related developments, but also of an ethically engaged research in sustainability problem-solving as well as policy analyses.